Effectiveness Of Seesaw As A Digital Learning Innovation To Improve Student Information Literacy - Uswatun Hasanah; Zulela; Edwita; Ahmad Januar; Agung Perdana (INVENTA: Jurnal Pendidikan Guru Sekolah Dasar, 2020)
This study aims to analyze the effectiveness of seesaw as a digital learning innovation to improve student information literacy. This type of research method used is a quantitative method with a quasi-experimental design and uses a one-group pretest-posttest with control group design. The sample used was 100 second semester students of Elementary School Teacher Education, Jakarta State University selected with technique a probability sample. The results of this study prove that the use of-based digital learning seesaw obtained significant values ​​so that it is effectively used in improving student information literacy. This digital learning design requires students to be selective in analyzing and evaluating information generated from different sources. This research can be used as input for education practitioners, especially lecturers in developing learning that adapts to the needs of the times and still requires students to have information literacy.